Surface modification of TiC-NiCrAl hard alloy by pulse electron beam; IEEE Transactions on Plasma Science; Vol. 37, iss. 10 - Koval N. N. Nikolay Nikolaevich; Ivanov Yu. F. Yuriy Fedorovich; Ovcharenko V. E.; Kolubaeva Yu. A.; Gngoryev S. V (2009, 2009)
Title screen